Innovations Products Children Working Brand Bilbil Kids in CV. Bilbil Berkah Sejahtera Bandung - Wahyudi, Indra; Djatmiko, Budi (International Journal of Business, Management and Economics, 2024)
Children's clothing is an important part of the fashion industry, which continues to grow. In recent years, innovation in children's clothing design and production has become a major focus for designers and manufacturers. This research aims to explore the latest innovations in children's clothing products, including designs adapted to children's development. The method used in this research is a comprehensive qualitative method from the results of analysis of several brands of children's clothing and interviews. It was found that forms of product innovation and innovative product development in Bilbil Kids prioritize the quality of raw materials for clothing and also product development is carried out using technical techniques. Sewing or sewing patterns used and speed in ordering custom clothing